Optical frequency comb generation techniques: An overview - Shoukat, Adeel; Munir, Abid; Niazi, Shahab Ahmad; Ahmad, Zulfiqar (Opto-Electronics Review, 2026)
Multi-carrier signal generation techniques are important in various photonic application domains. Multi-carrier sources having stable frequency responses, narrow line width and adequate spectral flatness can be used instead of laser arrays. One of the major applications of multi-carrier sources relates to high-speed optical communication networks. Optical systems such as orthogonal frequency division multiplexed (OFDM) and dense wavelength division multiplexed (DWDM) systems transmit information using multiple carriers on a single channel to improve the spectral efficiency of the transmission system. Traditional systems use multiple laser sources to generate multi-carriers, one for each channel with minimal phase coherence. Optical frequency combs (OFCs) generate optical subcarrier/carriers from a single laser source with improved phase and space coherence using different electro-optic schemes. Contrary to standard lasers, OFCs-based optical carriers provide reduced cost, flexibility, and improved spectral efficiency. In recent years, numerous publications have reported a variety of techniques to implement OFC and have succeeded in generating a wide range of carriers. For a comprehensive understanding of OFCs, it is essential to summarise and compare the techniques from a practical perspective, emphasising their real-world applications, advantages, and limitations. This review examines the characteristics of optical multi-carrier generators, providing a detailed comparison of different techniques. Furthermore, the transmission properties of these methods are analysed with focus on key practical factors, including flexibility, cost-efficiency, and power consumption. Lastly, potential challenges and future research directions relevant to real-world implementations are highlighted in this review.